To what extent are digital health interventions targeting HIV care cascade among mobile populations feasible, acceptable, and effective? A mixed methods systematic review protocol - Thulile Mathenjwa; Bessie Malila; Lucia Knight; Frank Tanser; Patricia Makwambeni; Tamsin K. Phillips (Systematic Reviews)
Abstract Introduction Human mobility is associated with an increased risk of HIV acquisition and disengagement from HIV care, leading to poorer health outcomes among highly mobile individuals compared to less mobile individuals. Mobile individuals, broadly defined as those who temporally, seasonally, or permanently move from one place to another for voluntary or involuntary reasons, face many challenges in accessing HIV care services. These challenges include logistical difficulties, interruptions in HIV care continuity, and limited access to services across different locations, which together hinder timely testing, treatment initiation, and viral suppression. Digital health interventions offer flexible approaches that can adjust to the mobile individual’s location to improve HIV care engagement and health outcomes for this underserved and hard-to-reach population. However, evidence on the feasibility, acceptability, and efficacy of digital health interventions across the HIV care cascade among mobile populations has not yet been appraised. Objectives We seek to synthesize empirical evidence on the feasibility, acceptability, and efficacy of digital health interventions targeting the HIV care cascade among mobile populations. Methods We will conduct a mixed methods systematic review of peer reviewed studies published between 1 January 2010 and 31 July 2024 that evaluated digital health interventions targeting the HIV care cascade among mobile populations. We will search PubMed, Web of Science, and EBSCOhost (Academic Search Premier, Africa-Wide information, CINAHL, Health Source: Nursing/Academic Edition, APA PsycInfo, APA PsycArticles) electronic databases. Bibliographies of retrieved studies will also be reviewed for relevant citations. Only studies published in English language and involved a digital health intervention, report an outcome related to the HIV care cascade, and involve mobile populations either partially or completely will be included. Two reviewers will independently screen titles and abstracts against the inclusion criteria, followed by full text screening for eligible articles. In case of disagreements, consensus will be sought from a third reviewer. Data synthesis will follow the Joanne Briggs Institute’s convergent segregated approach. If sufficient quantitative studies with comparable outcome measures are available, a meta-analysis will be performed. Discussion This review will address a critical evidence gap by consolidating data on digital health interventions’ feasibility, acceptability, and efficacy across the HIV care cascade among mobile populations. The results will inform the development of tailored digital health interventions to enhance HIV care delivery and health outcomes for this hard-to-reach population, supporting global HIV prevention and treatment goals. Systematic review registration This protocol is registered on PROSPERO (CRD42024528122).